The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3389/fmicb.2023.1138016
|View full text |Cite
|
Sign up to set email alerts
|

Progress on innate immune evasion and live attenuated vaccine of pseudorabies virus

Abstract: Pseudorabies virus (PRV) is a highly infectious disease that can infect most mammals, with pigs as the only natural host, has caused considerable economic losses to the pig husbandry of the world. Innate immunity is the first defense line of the host against the attack of pathogens and is essential for the proper establishment of adaptive immunity. The host uses the innate immune response to against the invasion of PRV; however PRV makes use of various strategies to inhibit the innate immunity to promote the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 166 publications
0
4
0
Order By: Relevance
“…However, several questions require clarification: (1) Further investigations should be performed to confirm the antiviral activities of these cellular factors against PRV in vivo. (2) It has been reported that PRV tegument proteins and glycoproteins can suppress the innate immune responses induced by virus infection ( 45 ). Such as PRV UL24, which can directly inhibit the transcription of multiple interferon-stimulated genes (e.g., OASL and ISG20 genes) ( 46 ).…”
Section: Perspective and Concluding Remarksmentioning
confidence: 99%
“…However, several questions require clarification: (1) Further investigations should be performed to confirm the antiviral activities of these cellular factors against PRV in vivo. (2) It has been reported that PRV tegument proteins and glycoproteins can suppress the innate immune responses induced by virus infection ( 45 ). Such as PRV UL24, which can directly inhibit the transcription of multiple interferon-stimulated genes (e.g., OASL and ISG20 genes) ( 46 ).…”
Section: Perspective and Concluding Remarksmentioning
confidence: 99%
“…8,9 Therefore, it is still a major challenge for veterinary immunology to formulate novel PRV vaccines that are both efficient and affordable. 10 Compared to live-attenuated vaccines, inactivated PRV vaccinations, as is known, are safe and noncontagious. However, their poor immunogenicity leads to unsatisfactory innate and adaptive immune responses for combating the PRV pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudorabies virus (PRV) is extremely infectious in mammals and poses a risk of spill-over transmission to humans ( 1 ) and considerable public health challenges. PRV can inhibit host innate immunity and promote viral replication ( 2 ). Thus, focusing more on immunity regularity is important for investigating the effect of PRV.…”
Section: Introductionmentioning
confidence: 99%